1995
DOI: 10.7326/0003-4819-123-9-199511010-00005
|View full text |Cite|
|
Sign up to set email alerts
|

Article RETRACTED: Changes in Energy Balance and Body Composition at Menopause: A Controlled Longitudinal Study

Abstract: Natural menopause is associated with reduced energy expenditure during rest and physical activity, an accelerated loss of fat-free mass, and increased central adiposity and fasting insulin levels. These changes may indicate a worsening cardiovascular and metabolic risk profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
280
5
36

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 477 publications
(331 citation statements)
references
References 0 publications
10
280
5
36
Order By: Relevance
“…Anabolic hormones such as growth hormone (GH), testosterone, and estrogen are reduced with age, and the withdrawal of their trophic effects may lead to muscle atrophy and sarcopenia. As mentioned earlier, there is evidence of accelerated loss of lean mass (and gain in fat) around menopause, suggesting that estrogen could have a role in supporting muscle mass (Poehlman et al, 1995). In addition, estrogen and testosterone have been shown to suppress catabolic cytokine expression in animal models, and may have an indirect role in modulating subclinical in¯ammation in aging (see below).…”
Section: Humoral Factorsmentioning
confidence: 87%
See 1 more Smart Citation
“…Anabolic hormones such as growth hormone (GH), testosterone, and estrogen are reduced with age, and the withdrawal of their trophic effects may lead to muscle atrophy and sarcopenia. As mentioned earlier, there is evidence of accelerated loss of lean mass (and gain in fat) around menopause, suggesting that estrogen could have a role in supporting muscle mass (Poehlman et al, 1995). In addition, estrogen and testosterone have been shown to suppress catabolic cytokine expression in animal models, and may have an indirect role in modulating subclinical in¯ammation in aging (see below).…”
Section: Humoral Factorsmentioning
confidence: 87%
“…These observations raise the question of whether menopause accelerates sarcopenia as it does osteopenia. A small study by Poehlman et al suggests that this is indeed the case, as women who experienced menopause had a much greater decline in lean body mass, gain in fat mass, and drop in metabolic rate than did women of similar ages who continued to have menses (Poehlman et al, 1995).…”
Section: Epidemiology Of Sarcopeniamentioning
confidence: 99%
“…However, studies using radiologic techniques such as computed tomography or dual x-ray absorptiometry (DEXA) showed that menopause may lead to the accumulation of intra-abdominal fat tissue (Tremollieres et al, 1996;Toth et al, 2000). What is more, Page 11 of 21 A c c e p t e d M a n u s c r i p t data from the few longitudinal studies suggest that menopause predisposes to the development of central obesity (Poehlman et al, 1995;Bjorkelund et al, 1996).…”
Section: Menopause Hormonal Changes and Obesitymentioning
confidence: 99%
“…Also, it has been shown that hypoestrogenemia in ovx rats causes central leptin insensitivity and increases hypothalamic neuropeptide Y levels and thereby contribute to excess fat accumulation (Ainslie et al, 2001). Results from human studies have also demonstrated that women who became postmenopausal had significantly greater reductions in resting metabolic rate and lower physical activity levels compared to their premenopausal controls (Ravussin et al, 1988;Poehlman et al, 1995). Other factors involved in fat metabolism are also likely to be involved.…”
Section: Menopause Hormonal Changes and Obesitymentioning
confidence: 99%
See 1 more Smart Citation